Overview of Burn Injury in Srinagarind Hospital : A preliminary Report - Komthong, Ronachai; Taksaphan, Prayong; Sittikesorn, Jirayu; Rungsitiyakul, Roongtiwa; Vatanasapt, Vanchai (Srinagarind Medical Journal, 2013)
Srinagarind Hospital is the only university hospital in the upper Northeastern region of Thailand. The burn unit section has been set up for more than 5 years already, but the allocated space is only 4 beds in a single room with 2 isolated room available providing for both severe burn and other appropriate general surgical cases as well. Regarded as the tirtiary center for the referring system in this region, a great number of major burn cases from regional provinces have been referred here. An overiew of burn injury regarding age, sex, incidence, cause, severity of injury, mortality and bacteriology were reviewed. This study is only the preliminary study to express an overview of burn injury in this hospital during a 3 year period.